Pengaruh Pelatihan Quantum Learning Terhadap Minat Belajar Ilmu Pengetahuan Alam Pada Siswa Sekolah Dasar - Nadea Zulfa Khairunnosa; R Rachmy Diana (JIP (Jurnal Intervensi Psikologi), 2018)
This study aims to examine the influence of quantum learning training on increasing interest in science learning to students. Subjects in this study were 8 students of class IV SD Negeri Ponjong II Gunungkidul Daerah Istimewa Yogyakarta with less learning interest in science subject. The data was analized by a scale of interest in learning science subject with GUTMANN scale model compiled by researchers. Experimental designed employed was pretest – posttest control group design. Subject in this study was randomly divided in two group, experiment group and control group that consist of 4 subjects in each groups. Mann Whitney U was used to analize the differences between the pretest, posttest, and follow up  from gained score.  The result of score analysis   pretest – posttest was 0,021 and pretest – follow up score was 0,020 ( p <  0,05), mean rank of experiment group was 6,50 and mean rank of controlt group was 2,50 which indicated that experiment group has a higher level of interest in learning science. This showed that quantum learning training could increase student’s interest in learning science subject at SD Negeri Ponjong II Gunungkidul Daerah Istimewa Yogyakarta.